Fish marketing in Miagao. - Maramba, Gilbert S.
This paper analyzed the performance of marketing intermediaries in Miag-ao through costs and returns analysis., The study described the profile and marketing pratices of twenty two (22) fish Marketing Intermediaries. To give a better analysis. Marketing intermediaries were divided into five groups - wholesaler-retailers, ordinary retailers, atado retailers, producer retailers, and itinerant retailers. The study showed that all types of marketing intermediary had a positive financial profit. However, Atado retailers had a negative economic profit at ( P 0.06 ). The P6.46 followed by the ordinary retailers at P 2.31. Producer-retailers and itinerant retailers had a P 1.56 and P 1.04 economic profit, respectively.